2014
DOI: 10.3384/diss.diva-110015
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Product Service Offerings for Rail and Road Infrastructure : Reviewing Applicability in Sweden

Abstract: This research aims to explore and propose a more effective management of rail and road infrastructure and the possibility of a more resource-efficient road and rail infrastructure by applying business models based on performance and a life-cycle perspective.There is a lack of efficiency in the Swedish rail and road infrastructure industries -at the same time as the availability of the rail tracks and roads is essential. Rail and road infrastructure have long lifetimes, around 40-60 years, and during these deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…This requires revising the specifications from a detailed component/technical level to a system/functional level. Performance-based contracts have been proposed in research literature as a method for increasing efficiency (Famurewa et al, 2012;Lingegård, 2014) and positive experiences have been reported from countries like The Netherlands. Alexandersson (2015, Section 8.3.2, pp.…”
Section: Contract Typesmentioning
confidence: 99%
“…This requires revising the specifications from a detailed component/technical level to a system/functional level. Performance-based contracts have been proposed in research literature as a method for increasing efficiency (Famurewa et al, 2012;Lingegård, 2014) and positive experiences have been reported from countries like The Netherlands. Alexandersson (2015, Section 8.3.2, pp.…”
Section: Contract Typesmentioning
confidence: 99%
“…The construction of physical infrastructure systems is an expensive and complex process with both social and environmental implications. Site and project conditions impact the construction phase of infrastructure systems such as roads and railway and should be consider when assessing the quantitative sustainability performance (Lingegård, 2014;Petkovic et al, 2004). These conditions could also affect the other life cycle phases of the systems.…”
Section: Challenges Of Quantitative Assessments Of Infrastructurementioning
confidence: 99%
“…Procurement of maintenance is often made in the form of medium-term contracts based on fixed price on defined work in the Swedish railway (Esping and Olsson, 2004). These kinds of contracts are quite inflexible and can easily lead to negotiations for all activities not included in the basic contract (Lingeg ard, 2014). There is little if no incentives for improving neither maintenance internal effectiveness nor its performance, as the contract is regulated on detailed level (Lingeg ard, 2014;Abdi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These kinds of contracts are quite inflexible and can easily lead to negotiations for all activities not included in the basic contract (Lingeg ard, 2014). There is little if no incentives for improving neither maintenance internal effectiveness nor its performance, as the contract is regulated on detailed level (Lingeg ard, 2014;Abdi et al, 2014). New forms of collaborative contracts have been tested in the Swedish railway industry, see e.g.…”
Section: Introductionmentioning
confidence: 99%